THE ROLE OF PRODUCTIVE SKILLS: SPEAKING AND WRITING IN LANGUAGE LEARNING (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Productive skills, primarily speaking and writing, play a crucial role in language learning. These skills allow learners to express their thoughts, ideas, and emotions effectively. This article explores the significance of speaking and writing in language acquisition, the challenges learners face, and effective strategies for enhancing these skills. By understanding the importance of productive skills, educators can better facilitate language learning and equip students with essential communication tools.